Ethnic Identity and Shopping Orientations among Chinese and Malay Consumers in Penang - Tang, Su Furn (2004)
The main purposes of this research are to investigate the role of ethnic identity and acculturation as a determinant of Chinese and Malay consumers approach to the marketplace and the factor ultimately related to consumer preferences information sources. There are few variables were focused in this research, which are ethnic identity, acculturation, information sources, and shopping orientations. A total of one hundred and ninety two respondents were classified into two groups based on their ethnicity: Chinese and Malay. Mall intercept interview method was used for this research. Analysis of variance and mean were utilized to determine whether the two ethnic groups differed with respect to shopping orientation and information sources. The findings showed a significant role of ethnic identity as determinant of shopping orientation. Malay and Chinese have differential preferences on information sources and shopping orientations. There were significant differences between shopping orientations and age groups, type of primary school attended and languages spoken at home. This research has provided basic for future research on ethnicity marketing and shopping orientation.